Clinical indication and timing of antenatal corticosteroid administration at a single centre. (20th October 2015) - Levin, HI; Ananth, CV; Benjamin‐Boamah, C; Siddiq, Z; Son, M; Friedman, AM
Abstract : Objective: To determine how well antenatal corticosteroids (ACS) were timed, based on the indication for administration for women delivering preterm. Design: Retrospective cohort study. Setting: Tertiary medical centre. Population: Six hundred and thirty women who had singleton preterm births between 24 and 34 weeks' gestational age. Methods: Charts from 2006 to 2011 were reviewed for indications for ACS administration, which included premature rupture of membranes, threatened preterm labour, risk factors for spontaneous preterm birth such as short ultrasound cervical length, positive fetal fibronectin, and hypertensive disorders of pregnancy. Charts were reviewed for timing of ACS administration in relation to delivery. Main outcome measures: The primary outcome was optimal timing, defined as administration of ACS ≥24 hours to ≤7 days prior to delivery. Results: Of 630 women who delivered preterm, 589 (93%) received ACS prior to delivery. ACS timing was optimal in 40% (238 of 589) of cases. Women with hypertensive disorders were most likely to have steroids optimally timed (62%). Asymptomatic women at increased risk for preterm delivery were less likely to receive optimally timed ACS (12%). The majority of women who received steroids >2 weeks prior to delivery (57%) received a second course. Conclusion: A majority of women who delivered preterm did not receive optimally timed ACS. Diagnostic tools that identified women at risk for preterm birth were not able to identify patients for appropriate steroid timing. Given the range of clinical scenarios in which patients are at increased risk for preterm delivery, further research is needed to assist clinicians in optimising steroid administration. Tweetable abstract: Optimal timing of antenatal steroids prior to delivery does not occur in most cases. Tweetable abstract: Optimal timing of antenatal steroids prior to delivery does not occur in most cases. This article includes Author Insights, a video abstract available athttps://vimeo.com/151534373